Kształtowanie się systemu politycznego i proces transformacji ustrojowej Armenii - Fedorowicz, Krzysztof (Fundacja na rzecz Czystej Energii, 2016)
The Author analyses the process of transformation in Armenia. It indicates the socio-political factors the formation of political system of Armenia. The first formative period of independence was difficult. It is a time of war and political and economic isolation in the international arena. These events have a huge impact on the formation of a model of institutional and legal state. From the beginning force and violence has become one of the important mechanisms for achieving political goals, with the result that Armenian political system today is characterized by a low stability and a high degree of susceptibility to disturbances and conflicts. The process of transformation of the political system of Armenia is still going. It takes time, and above all the political will of the current elite, took to the characteristics of transparency and maturity characterizing political systems of democratic states.
Formation of the Political System and the Proces of Political Transformation of Armenia
Keywords: Armenia; system polityczny